PRODUKSI ENZIM SELULASE KASAR DARI BAKTERI SELULOLITIK - Nababan, Monalisa; Gunam, Ida Bagus Wayan; Mahaputra Wijaya, I Made (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 7 No 2 (2019): Juni, 2019)
The purpose of this research was to elucidate the potentials of cellulolytic bacteria isolates in producing crude cellulose enzymes and to determine the ability of exoglucanase enzymes and endoglucanase enzymes produced from selected cellulolytic bacteria isolates. Ten potential isolates from previous research were confirmed using 1% Carboxymethyl Cellulose (CMC) media with the addition of Congo red and four potential isolates were obtained which then crude cellulose production and enzyme activity tests were carried out using cellulose substrates such as Carboxymethyl Cellulose (CMC), and Filter Paper (FP) Whattman number 1. The exoglucanase enzyme activity was obtained between 0.069 IU/mL to 0.072 IU /mL. The activity test of endoglucanase enzyme was obtained between 0.069 IU / mL to 0.074 IU/mL. Cellulose degradation was obtained between 3.32% to 11.37%. Isolate that have the highest enzymatic activity and cellulose degradation ability was B2S8. Keywords : Cellulolytic bacteria, Cellulase enzyme, Enzyme activity, Congo red.